Risk of respiratory syncytial virus infection in infants with congenital cystic lung disease. Issue 2 (24th February 2015) - Hama, Ikuko; Takahashi, Shigehiro; Nakamura, Tomoo; Ito, Yushi; Kawasaki, Kazuteru; Sago, Haruhiko
Abstract Background Congenital cystic lung disease (CCLD), which includes congenital cystic adenomatoid malformation, bronchopulmonary sequestration, and congenital lobar emphysema, has been reported to increase the risk of recurrent respiratory infection. In particular, respiratory syncytial virus (RSV) causes severe lower respiratory tract disease in high‐risk infants. The objective of this study was to investigate the risk of severe RSV infection in infants with CCLD. Methods Infants antenatally diagnosed as having CCLD and admitted to a neonatal intensive care unit at the National Center for Child Health and Development in Tokyo between September 2002 and October 2011 were included in this study. We investigated retrospectively whether the infants were hospitalized with RSV infection by 24 months of age using their medical records. Results Forty‐eight infants were antenatally diagnosed as having CCLD. Of the 48 infants, four (8.3%) were hospitalized with RSV infection by 24 months of age. Conclusions Infants with CCLD have increased risk of severe RSV infection.